Genesis of initial defects in the process of monocrystalline silicon oxidation with subsequent scribing - Smyntyna, V.A.; Sviridova, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The type, density, and distribution of defects in initial and oxidated monocrystalline silicon wafers were studied by modern methods. It was established that disordered silicon and stacking faults are basic defects in near-surface layers of oxidated monocrystalline silicon. It was shown that stacking faults are generated during the oxidation process, and the mechanism of their formation is connected with the defective layered structure of initial silicon wafers. It was established that defects of layered heterogeneity, on the one hand, lead to the formation of stacking faults and, on the other hand, prevent their propagation to the wafer bulk.